Los pasos perdidos as Lost World Fiction - Harney, Lucy D. (2013)
The narrator of Carpentier’s Los pasos perdidos (1953) has intrigued and confounded scholars and critics since at least the early 1970s, when Roberto González Echevarría pointed to what he characterized as a dissonance in the novel’s narrative voice. The present analysis challenges primarily autobiographical interpretations of the novel which have emerged in recent years, arguing instead for a parodic narrative voice that unwittingly appropriates, among other traditions, the popular genre of lost world fiction.